Tax Payers’ Knowledge Towards Value Added Tax in Nepal - Gnawali, Achyut (Journal of Nepalese Business Studies, 2018)
Value added tax (VAT) has been the most essential choice as an ingredient of tax reforms of developing countries like Nepal, which leads to revenue enhancement and sustainable economic development. As VAT was a new concept in Nepal, a comprehensive taxpayer education program was launched to impart knowledge regarding the various aspects of VAT to parliamentarians, industrialists, businesspersons, consumers as well as various sections of the society. The study used descriptive and survey research design. Data were collected through questionnaires. Statistical tools were used to make a proper analysis. It is found that more than 88 percent of respondents are aware enough to ask tax invoice after purchasing goods or services. Most of them ask for tax invoice to get the authenticity of sellers. VAT must be successful and this largely depends upon the public awareness, honesty, faith and morality of tax officials and the business community. There is a need for willpower and action. It is also found that taxpayers’ awareness programme and tax education play prime role to increase the VAT revenue in Nepal.